Bilateral Tubal Gestation Associated with Schistosomiasis in an African Woman - K. H. Odubamowo; O. M. Akinpelu; O. O. Lawal; C. A. Okolo; A. A. Odukogbe; A. O. Adekunle (Case Reports in Obstetrics and Gynecology)
Background. The incidence of tubal ectopic gestation caused by schistosomiasis induced tubal pathology is undocumented in this environment, which may be due to rarity of this pathology. Bilateral tubal gestation is common in patients that have undergone in vitro fertilization. We report a hitherto undocumented case of spontaneous bilateral ectopic gestation following tubal schistosomiasis. Case Report. Mrs. OB was a 32-year-old G4P3+0 (3 alive) woman who complained of abdominal pain and bleeding per vaginam of 4 and 2 days’ duration respectively following 8 weeks of amenorrhea. A clinical impression of ruptured ectopic gestation was confirmed by ultrasound scanning. She had bilateral salpingectomy with histology of specimens showing bilateral ectopic gestation with Schistosoma haematobium induced salpingitis (findings of Schistosoma haematobium ova noted on slide). Conclusion. Schistosoma induced salpingitis is a rare but possible cause of bilateral tubal gestation.